1991
DOI: 10.1001/jama.1991.03470220075030
|View full text |Cite
|
Sign up to set email alerts
|

Active Enforcement of Cigarette Control Laws in the Prevention of Cigarette Sales to Minors

Abstract: Cigarette control laws can be effective in significantly reducing the rate of cigarettes sold by merchants and rates of cigarette use by adolescents. Key elements of successful legislation implementation are consistent compliance checking and heightened community awareness of the problems and prevalence of adolescent smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
97
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(99 citation statements)
references
References 3 publications
1
97
1
Order By: Relevance
“…More specifically, two multi-community interventions found that instituting compliance checks improved compliance somewhat, but had little effect on perceived access and no effect on smoking behavior (Altman et al, 1999;Rigotti et al, 1997), and another communitywide intervention yielded no effect even on compliance (Lewis et al, 1996). Yet another communitywide intervention, which included both compliance checks and community education, yielded improved compliance and reduced use of stores (Jason et al, 1991(Jason et al, , 1999a. However, that intervention had no effect on age of initiation or amount of smoking (Jason et al, 1999a(Jason et al, , 1999b, although it may have reduced the prevalence of regular smokers (Jason et al, 1991(Jason et al, , 1999a.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, two multi-community interventions found that instituting compliance checks improved compliance somewhat, but had little effect on perceived access and no effect on smoking behavior (Altman et al, 1999;Rigotti et al, 1997), and another communitywide intervention yielded no effect even on compliance (Lewis et al, 1996). Yet another communitywide intervention, which included both compliance checks and community education, yielded improved compliance and reduced use of stores (Jason et al, 1991(Jason et al, , 1999a. However, that intervention had no effect on age of initiation or amount of smoking (Jason et al, 1999a(Jason et al, , 1999b, although it may have reduced the prevalence of regular smokers (Jason et al, 1991(Jason et al, , 1999a.…”
mentioning
confidence: 99%
“…Yet another communitywide intervention, which included both compliance checks and community education, yielded improved compliance and reduced use of stores (Jason et al, 1991(Jason et al, , 1999a. However, that intervention had no effect on age of initiation or amount of smoking (Jason et al, 1999a(Jason et al, , 1999b, although it may have reduced the prevalence of regular smokers (Jason et al, 1991(Jason et al, , 1999a. Other interventions have yielded similarly inconsistent or inconclusive effects on smoking behavior (DiFranza et al, 1992;Hinds, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are notable exceptions in our field. For example, Jason, Ji, Anes, & Birkhead (1991) scrutinized how legislative changes on tobacco access-an environmental intervention-reduced smoking rates of minors by 50%. Importantly, this form of intervention runs counter to many programs that focus on educating and socializing students away from tobacco use.…”
Section: Community Psychology As a Vehicle For Systems Changementioning
confidence: 99%
“…In Buffalo, New York, educational efforts had no effect on retail store tobacco sales to minors (Altman et al, 1989), and an educational campaign in Santa Clara, California, showed only a short-term reduction in sales (Altman, RasenickDouss, Foster, & Tye, 1991). Jason and colleagues (Jason, Ji, Anes, & Birkhead, 1991) reported a substantial impact of a merchant-oriented program. However, their approach included legislative and enforcement strategies in addition to the traditional educational approach.…”
mentioning
confidence: 99%